Evaluating internet-based Cognitive Behavioural Therapy (CBT) for body dysmorphic disorder: a systematic review - Jabeen, Mehwish; Shahzadi, Mafia; Hussain, Aftab; Unbrin, Aqila; Ehsaan, Saba (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the effectiveness, cost-effectiveness and feasibility of internet-based Cognitive Behavioural Therapy (CBT) in the treatment of body dysmorphic disorder. Method: The systematic review was conducted from August 19 to September 22, 2023, and comprised search on Cochrane Library, Embase, Google Scholar, PubMed, PsycINFO and Web of Science databases using specific key words for studies published in the English language from 2010 onwards. Grey literature and pertinent conference proceedings were also searched to include as many studies as possible that investigated internet-based cognitive behavioural therapy in the treatment of body dysmorphic disorder. Data extraction was done, and the selected studies were subjected to quality assessment, followed by a narrative synthesis of the findings. Results: Out of the 6,837 studies initially identified, 8(0.11%) were analysed in detail. Of the 8 studies, 4(50%) were RCTs, while 5(62.5%) had been conducted in Sweden. Therapist-guided internet-based cognitive behavioural therapy interventions consistently demonstrated efficacy with respect to reducing body dysmorphic disorder symptom severity, improving insight, and enhancing quality of life. Cost-effectiveness analyses highlighted the favourable economic aspect of internet-based cognitive behavioural therapy. Feasibility and acceptability were demonstrated by high participant engagement and satisfaction. Conclusion: Internet-based cognitive behavioural therapy showed promise in addressing the treatment gap in body dysmorphic disorder care, offering accessible, cost-effective and feasible interventions. Key Words: Body dysmorphic disorder, Cost-effectiveness, Efficacy, Feasibility, Internet-based cognitive behavioural therapy.